Frequency of Drug Resistance Among Retreatment Tuberculosis Patients in Gulab Devi Chest Hospital - ZAHEER AKHTER, M. JAMIL, M. AQEEL UR REHMAN, USMAN JAVED IQBAL (Journal of Fatima Jinnah Medical University, 2018)
Objective: Emerging drug resistance is a global challenge. Efforts are underway to detect and treat this menace. We carried out this study to ascertain the frequency of MDR among Category-II pulmonary TB patients. Methodology: In this cross-sectional descriptive study all MTB detected cases admitted in hospital OR being referred in OPD were included in the study. CAT-II cases subjected to GeneXpert analysis to detect MDR in terms of Rifampicin resistance. Including basic demographic details all the data were recorded in a short structured questionnaire. Results: A total of 1085 MTB detected patients were included in this study. There was an overall male predominance (53%). Majority of our patients were in the range of 15-45 years of age. Out of 1085 patients Category-II treated patients were accounting 38% (411) of the total MTB cases. Rifampicin resistance was detected in 211 (54%) cases of the total Category-II treated patients. Conclusion: Over all frequency of MDR in Category-II treated patients was 54%. Primary drug resistance was a strong risk factor for failure and relapse and for acquiring further resistance. As 59% of failure cases had RIF resistance, the standard re-treatment regimen appears inadequate for failure cases.